Standardization and validation of a western blot for the diagnosis of human immunodeficiency virus: Estandarización y validación de un western blot para el diagnóstico del virus de inmunodeficiencia humana - Miranda Ulloa, Eduardo F. (2021)
Objectives: To standardize and validate a western blot test for the diagnosis of human immunodeficiency virus. Methods: A prospective observational study was carried out during 2017 and 2018. The western blot test was standardized, using the polyacrylamide gel electrophoresis technique with sodium dodecyl sulfate (SDS PAGE), being the nitrocellulose blot strips prepared with an Optimal HIV-1 antigen concentration of 2.71 µg / mm. The western blot was validated in the laboratory against 400 reference samples (300 sera and 100 plasmas): 200 positive and 200 negatives for antibodies against HIV-1, being the reference test the Immunoblot of the Fujirebio brand. Diagnostic performance parameters were estimated using Epidat v3.1 and Excel. Results: Eight important bands of the HIV-1 antigen were identified: p17, p24, p31, p39, gp41, p55, p66, and gp120. According to the Consortium for the normalization of serology for retroviruse, those that were taken as specific diagnostic bands were: p24, p31, gp41, and gp120. The sensitivity, specificity, positive and negative predictive value and validity index against sera were: 96.7%, 96.0%, 96.0%, 96.6%, 96.3%; and against plasmas: 98.0%, 100.0%, 100.0%, 98.0%, 99.0% respectively. No false positives and negatives were found, but some were undetermined. Conclusion: The development of this western blot test with proprietary technology presented similar diagnostic performance to the reference test, without showing cross-reactions, being useful for confirming HIV.